The human P2X7 receptor alters microglial morphology and cytokine secretion following immunomodulation - von Mücke-Heim, Iven-Alex; Martin, Jana; Uhr, Manfred; Ries, Clemens; Deussing, Jan M. (Frontiers in Pharmacology, 2023)
In recent years, purinergic signalling via the P2X7 receptor (P2X7R) on microglia has repeatedly been implicated in depression genesis. However, it remains unclear which role the human P2X7R (hP2X7R) plays in regulating both microglia morphology and cytokine secretion upon different environmental and immune stimuli, respectively. For this purpose, we used primary microglial cultures derived from a humanized microglia-specific conditional P2X7R knockout mouse line to emulate different gene-environment interactions between microglial hP2X7R and molecular proxies of psychosocial and pathogen-derived immune stimuli. Microglial cultures were subjected to treatments with the agonists 2'(3')-O-(4-benzoylbenzoyl)-ATP (BzATP) and lipopolysaccharides (LPS) combined with specific P2X7R antagonists (JNJ-47965567, A-804598). Morphotyping revealed overall high baseline activation due to the in vitro conditions. Both BzATP and LPS+BzATP treatment increased round/ameboid microglia and decreased polarized and ramified morphotypes. This effect was stronger in hP2X7R-proficient (CTRL) compared to knockout (KO) microglia. Aptly, we found antagonism with JNJ-4796556 and A-804598 to reduce round/ameboid microglia and increase complex morphologies only in CTRL but not KO microglia. Single cell shape descriptor analysis confirmed the morphotyping results. Compared to KO microglia, hP2X7R-targeted stimulation in CTRLs led to a more pronounced increase in microglial roundness and circularity along with an overall higher decrease in aspect ratio and shape complexity. JNJ-4796556 and A-804598, on the other hand, led to opposite dynamics. In KO microglia, similar trends were observed, yet the magnitude of responses was much smaller. Parallel assessment of 10 cytokines demonstrated the proinflammatory properties of hP2X7R. Following LPS+BzATP stimulation, TNFα, IL-1β, IL-6, and IL-27 levels were found to be higher and IL-4 levels lower in CTRL than in KO cultures. Vice versa, hP2X7R antagonists reduced proinflammatory cytokines and increased IL-4 secretion. Taken together, our results disentangle the complex function of microglial hP2X7R downstream of various immune stimuli. In addition, this is the first study in a humanized, microglia-specific in vitro model identifying a so far unknown link between immune stimulation and inhibition, microglial hP2X7R function, and IL-27 levels.